Lectotypification of the name Thalictrum purdomii (Ranunculaceae) - Yuan, Qiong; Ren, Chen; Yang, Qin-Er (Phytotaxa, 2018)
Thalictrum purdomii Clark (1913: 39) was described on the basis of a gathering, W. Purdom 169 (K), which includes two plants grown from seeds collected from northern China. Wang & Wang (1980) pointed out that the two plants represent two different taxa, with one sheet (K000694124; Fig. 1) belonging to T. minus var. hypoleucum (Siebold & Zuccarini 1846: 178) Miquel (1867: 3) and the other (K000694123; Fig. 2) belonging to T. squarrosum Stephen ex Willdenow (1799: 1299). As a result, they cited T. purdomii as synonyms of both T. minus var. hypoleucum and T. squarrosum, not proposing a lectotypification for the name. Fu & Zhu (2001) cited T. purdomii as a synonym of only T. minus var. hypoleucum, but they also did not designate a lectotype for T. purdomii.